Maintenance of genome stability in plants: repairing DNA double strand breaks and chromatin structure stability - Roy, Sujit (Frontiers in Plant Science, 2014)
Plant cells are subject to high levels of DNA damage resulting from plant’s obligatory dependence on sunlight and the associated exposure to environmental stresses like solar UV radiation, high soil salinity, drought, chilling injury and other air and soil pollutants including heavy metals and metabolic byproducts from endogenous processes. The irreversible DNA damages, generated by the environmental and genotoxic stresses affect plant growth and development, reproduction and crop productivity. Thus, for maintaining genome stability, plants have developed an extensive array of mechanisms for the detection and repair of DNA damages. This review will focus recent advances in our understanding of mechanisms regulating plant genome stability in the context of repairing of double stand breaks and chromatin structure maintenance.